2012
DOI: 10.1136/bmj.e3260
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided corticosteroid injection for plantar fasciitis: randomised controlled trial

Abstract: Objective To investigate the effectiveness of ultrasound guided corticosteroid injection in the treatment of plantar fasciitis.Design Randomised, investigator and participant blinded, placebo controlled trial.Setting University clinic in Melbourne, Australia.Participants 82 people with a clinical and ultrasound diagnosis of plantar fasciitis unrelated to systemic inflammatory disease.Interventions Participants were randomly allocated to ultrasound guided injection of the plantar fascia with either 1 mL of 4 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
152
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(169 citation statements)
references
References 52 publications
11
152
2
4
Order By: Relevance
“…In the present analysis, two studies (8,10) reported that no adverse event occurred. This was not mentioned in two other studies (7,9).…”
Section: Quality Assessment -----------------------------------------mentioning
confidence: 87%
See 3 more Smart Citations
“…In the present analysis, two studies (8,10) reported that no adverse event occurred. This was not mentioned in two other studies (7,9).…”
Section: Quality Assessment -----------------------------------------mentioning
confidence: 87%
“…The incidence rate of the condition increases with age (13). In the present study, the average body mass index was mentioned in three studies (8)(9)(10) and ranged from 30.9 to 32.4 kg/m 2 . The incidence of plantar fasciitis in obese individuals has been found to be 5.6-fold higher than that in the non-obese (16).…”
Section: Quality Assessment -----------------------------------------mentioning
confidence: 99%
See 2 more Smart Citations
“…This has clinical implications regarding the management of plantar fasciitis, and suggests that some patients may respond well to treatments targeting neurovascular pain mechanisms, such as injection of corticosteroids or agents with direct sclerosing properties (eg, polidocanol). Furthermore, the findings of this study provide some explanation of the mechanism by which corticosteroids, which exert angiostatic effects (eg, inhibition of endothelial cell proliferation and migration), 21 have been shown to reduce pain 3 and tissue swelling 3,17 in plantar fasciitis over a 3-month period.…”
Section: Discussionmentioning
confidence: 99%